Development of sensorised tool for robotic manipulation of objects - Seetharaman, Yuvanesh (Nanyang Technological University, 2024)
This report would present the design, development, and integration of a self-adjusting sensorised tool for robotic arms to enhance its gripping capabilities on objects through wrist like movement. The integration of robotic arms into a variety of industries have significantly helped in boosting productivity and efficiency overall. However commonly robotic grippers often face difficulties when grasping objects with irregular shapes or uneven surfaces. The proposed sensorised tool addresses these issues by incorporating a dynamic ball and base mechanism that would autonomously adjust itself to be in full contact with the object to be moved. With a detailed literature review that explains the existing robotic grippers and mechanisms in use today and the challenges faced by them and a methodology section to elaborate the steps involved in developing the sensorised tool and the integration of sensors to further enhance the functionality of the tool. This report also explains the principles, features required, and the data collected from the experiments carried out, highlighting the possible uses that it would have especially in industrial use. Its ability to self adjust to objects with different orientiaons would improve the overall operational efficiency of processes. Moreover, with the constant advancements with artificial intelligence and sensor technology, there are also possibilities of further improvement in new iterations of the sensorised tool in the future.